Advancing adaptive governance of social-ecological systems through theoretical multiplicity. Issue 57 (March 2016) - Karpouzoglou, Timothy; Dewulf, Art; Clark, Julian
Highlights: A systematic review of adaptive governance scholarship is conducted for the period 2005–2014. Adaptive governance is a governance theory that combines analyses of novel governance capacities. The emphasis on adaptive capacity is a major strength of the theory. Theoretical multiplicity can support a more robust governance theory for a variety of contexts. Theoretical multiplicity improves evaluation of governance features, such as power and politics. Abstract: In recent years there has been rising scientific and policy interest in the adaptive governance of social-ecological systems. A systematic literature review of adaptive governance research during the period 2005–2014, demonstrates a vibrant debate taking place that spans a variety of empirical and theoretical approaches. The particular strength of adaptive governance is that it provides a theoretical lens for research that combines the analyses of novel governance capacities such as adaptive capacity, collaboration, scaling, knowledge and learning. As a way to give greater depth and analytical rigour to future studies over the next decade and beyond, we highlight the added value of theoretical multiplicity (i.e., focusing on the combination of theories to address complex problems). We argue that theoretical multiplicity can encourage stronger synergies between adaptive governance and other theoretical approaches and can help address epistemologically grey areas in adaptive governance scholarship, such as power and politics, inclusion and equity, short term and long term change, the relationship between public policy and adaptive governance.